Differential Responses of Cucurbita pepo to Podosphaera xanthii Reveal the Mechanism of Powdery Mildew Disease Resistance in Pumpkin - Zhang, Shuwu; Liu, Jia; Xu, Bingliang; Zhou, Jingjiang (Frontiers in Plant Science, 2021)
A number of strategies has been developed and applied to discover suitable and safer methods to manage the occurrence of powdery mildew disease in pumpkins (Cucurbita pepo L.), but information is limited in screening tolerant germplasms and exploring their mechanisms in preventing the disease occurrence at physiological, biochemical, and molecular levels. Therefore, we investigated the responses of two commercial pumpkin cultivars to Podosphaera xanthii infection. Compared with mock-inoculated seedlings, few small and sparse powdery area were observed on the leaves of Sixing F1 cultivar at the 13th day after inoculation with P. xanthii, whereas a large number of diseased powdery area and a layer of white powdery mildew were observed on the surface of Jin12 F1 leaves. The inoculation duration (7, 9, 11 and 13 days) significantly and continuously increased the disease incidence and index of pumpkin seedlings. The contents of H2O2, MDA, lignin and total phenolics in the leaves of Sixing F1 and Jin12 F1 cultivars were markedly increased after inoculation with P. xanthii. However, the Sixing F1 cultivar exhibited much less reactive oxygen species (ROS) accumulation, lower rate of lipid peroxidation, higher level of lignin and total phenolics contents after inoculation than the Jin12 F1 cultivar. Compared with untreated control pumpkin seedlings, significantly higher activities and gene expressions of the phenylpropanoids pathway enzymes (PAL and PPO), ROS scavenging defense enzymes (SOD, CAT, POD and APX) and other salicylic acid (SA) signaling pathway marker genes were observed in the leaves of both cultivars after P. xanthii inoculation at different inoculation time points. These enhancements were significantly higher in Sixing F1 than Jin12 F1. Our results indicate that the Sixing F1 cultivar exhibited a much stronger ability in resistance to P. xanthii infection than the Jin12 F1 cultivar. Our results suggest that one possible mechanism of C. pepo cultivars to prevent the pathogen P. xanthii infection is by activating and enhancing the activity and gene expression of the phenylpropanoids pathway to synthesize phenolic substances and lignin, and ROS scavenging defense enzymes to eliminate the harmful effects of ROS, and signaling pathway marker genes expression to improve plant disease resistance.